Inventario de las especies vegetales existentes en el Campus Matriz de la Universidad Técnica de Cotopaxi – Latacunga – provincia de Cotopaxi – 2022. - Villegas Bosque, Brayan Adrián (2022)
The present work consists of making an inventory of the existing plant species on the campus of the Technical University of Cotopaxi, taking into account that plants are a basic and elemental part of life on planet Earth. The Technical University of Cotopaxi at its headquarters campus is the destination of its 29,407.60 m2, of which 1,000 m2 are destined for green areas, which are distributed over 585 floors. Without them, life would be different both for humans and for other beings, which will contribute to the process of climate change since they provide shelter to many other living beings, they are capable of producing oxygen that we breathe, maintain the soil, regulate moisture and contribute to climate stability. They are the only ones capable of capturing the sun's energy to make organic matter and release oxygen. For this reason, they are indispensable for the life of other organisms. They are part of all ecosystems and have adapted to various climates and soil conditions. Some can live in very dry places, others need plenty of water. Therefore, in this inventory several plant species were identified such as: Ficus benjamina, Margarita, Gerbera, Taxus baccata, Callistemon citrinus, Iresine lindenii, Tecoma stans and Alnus glutinous, obtaining as a final result a total of 585 plant species fully cared for and in perfect condition within the Matrix campus, which were classified by families to identify to which they belong and determine which are the most appropriate species according to the climate, latitude and altitude required to incorporate them within the gardens of the Matrix campus, to obtain as a result environmentally friendly biodiversity. Given the imminent urban growth of the city of Latacunga, it is essential to diagnose the ecological reality that the main campus is experiencing, especially in order to generate solutions around the effects of climate change, encompassing the balance of green areas and existing trees in contrast to the number of inhabitants of the urban sector, guaranteeing coexistence and development in an ecologically balanced environment for the university population. In order to generate solutions, it is necessary to carry out an inventory of green areas, followed by georeferencing and characterization of plant species implemented by the Technical University of Cotopaxi, thus allowing the growth and conservation of green areas and trees that are efficient in absorbing CO2. Eradicate the existence of heat islands due to the alarming increase in greenhouse gas emissions.